The highly sensitive person ebook How to thrive when the world overwhelms you. - Aron, Elaine N. (2013)
The 25TH ANNIVERSARY EDITION of the original ground-breaking book on high sensitivity with over 500,000 copies sold. ARE YOU A HIGHLY SENSITIVE PERSON? Do you have a keen imagination and vivid dreams? Is time alone each day as essential to you as food and water? Are you noted for your empathy? Your conscientiousness? Do noise and confusion quickly overwhelm you? If your answers are yes, you may be a highly sensitive person (HSP) and Dr. Elaine Aron's The Highly Sensitive Person is the life-changing guide you'll want in your toolbox. Over twenty percent of people have this amazing, innate trait. Maybe you are one of them. A similar percentage is found in over 100 species, because high sensitivity is a survival strategy. It is also a way of life for HSPs. In this 25th anniversary edition of the groundbreaking classic, Dr. Elaine Aron, a research and clinical psychologist as well as an HSP herself, helps you grasp the reality of your wonderful trait, understand your past in the light of it, and make the most of it in your future. Drawing on her many years of study and face-to-face time spent with thousands of HSPs, she explains the changes you will need to make in order to lead a fuller, richer life. Along with a new Author's Note, the latest scientific research, and a fresh discussion of anti-depressants, this edition of The Highly Sensitive Person is more essential than ever for creating the sense of self-worth and empowerment every HSP deserves and our planet needs. "Elaine Aron has not only validated and scientifically corroborated high sensitivity as a trait—she has given a level of empowerment and understanding to a large group of the planet's population. I thank Dr. Aron every day for her having brought this awareness to the world." —Alanis Morissette, artist, activist, teacher